Limiting volume with modern ventilators. (June 2015) - Wing, Thomas J.; Haan, Lutana; Ashworth, Lonny J.; Anderson, Jeff
Background: The acute respiratory distress syndrome (ARDS) network low tidal-volume study comparing tidal volumes of 12 ml/kg versus 6 ml/kg was published in 2000. The study was stopped early as data revealed a 22% relative reduction in mortality rate when using 6 ml/kg tidal volume. The current generation of critical care ventilators allows the tidal volume to be set during volume-targeted, assist/control (volume A/C); however, some ventilators include options that may prevent the tidal volume from being controlled. The purpose of this bench study was to evaluate the delivered tidal volume, when these options are active, in a spontaneously breathing lung model using an electronic breathing simulator. Methods: Four ventilators were evaluated: CareFusion AVEA (AVEA), Dräger Evita® XL (Evita XL), Covidien Puritan Bennett® 840 TM (PB 840), and Maquet SERVO-i (SERVO-i). Each ventilator was connected to the Hans Rudolph Electronic Breathing Simulator at an amplitude of 0 cm H2 O and then 10 cm H2 O. All four ventilators were set to deliver volume A/C, tidal volume 400 ml, respiratory rate 20 bpm, positive end-expiratory pressure 5 cm H2 O, peak flowrate 60 L/min. The displayed tidal volume was recorded for each ventilator at the above settings with additional options OFF and then ON. Results: The AVEA has two options in volume A/C: demand breaths and V-sync. When activated, these options allow the patient to exceed the set tidal volume. When using the Evita XL, the option AutoFlow can be turned ON or OFF, and when this option is ON, the tidal volume may vary. The PB 840 does not have any additional options that affect volume delivery, and it maintains the set tidal volume regardless of patient effort. The SERVO-i's demand valve allows additional flow if the patient's inspiratory flowrate exceeds the set flowrate, increasing the delivered tidal volume; this option can be turned OFF with the latest software upgrade. Conclusions: Modern ventilators have an increasing number of optional settings. These settings may increase the delivered tidal volume and disrupt a low tidal-volume strategy. Recognizing how each setting within a mode affects the type of breath delivered is critical when caring for ventilator-dependent patients.